2017
DOI: 10.1017/s104161021700151x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild behavioral impairment in mild cognitive impairment and subjective cognitive decline, and its association with caregiver burden

Abstract: MBI was common in memory clinic patients without dementia and was associated with greater caregiver burden. These data show that MBI is a common and clinically relevant syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
149
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 33 publications
4
149
5
1
Order By: Relevance
“…Previous studies, using traditional NPS rating scales such as the NPI-Q, indicated that the NPS prevalence in MCI populations ranges from 35% up to 85% [7,8]. Using a transformation algorithm of the NPI score to capture criterion one of MBI, the prevalence estimated in two recent studies was 85.3% in a clinical sample [38] and 48.9% in a community sample [39]. These percentages are significantly higher than in our sample, possibly due to the short frame of reference of 1 month of symptoms, required by the NPI, compared to the more rigorous expectation of six months of symptom duration and later life onset of symptoms in the MBI-C.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, using traditional NPS rating scales such as the NPI-Q, indicated that the NPS prevalence in MCI populations ranges from 35% up to 85% [7,8]. Using a transformation algorithm of the NPI score to capture criterion one of MBI, the prevalence estimated in two recent studies was 85.3% in a clinical sample [38] and 48.9% in a community sample [39]. These percentages are significantly higher than in our sample, possibly due to the short frame of reference of 1 month of symptoms, required by the NPI, compared to the more rigorous expectation of six months of symptom duration and later life onset of symptoms in the MBI-C.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MBI in our study is an approximation of MBI Criterion 1, using a 1‐month reference range, and a rating scale designed for a dementia population as opposed to a community dwelling population health sample. While we have recently published prevalence data in community (Mortby, Ismail, et al, ) and clinical (Sheikh et al, ) samples using these criteria (Mortby, Ismail, et al, ; Sheikh et al, ), this transformation algorithm has yet to be validated against the MBI‐C. This is especially important for domains such as social appropriateness, which are nominally represented by the “disinhibition” item in the NPI, as opposed to more detailed questioning on empathy, tact, and social behavior as described in the MBI‐C.…”
Section: Discussionmentioning
confidence: 99%
“…In advance of that, an MBI transformation algorithm has been developed to map NPI (Cummings et al, ) items onto MBI domains, to approximate Criterion 1 of MBI (albeit with a 1‐month reference range), and to facilitate further study and analysis. This published algorithm has been used to generate MBI Criterion 1 prevalence estimates in community (Mortby, Ismail, et al, ; Sheikh et al, ) and clinical (Sheikh et al, 2018) samples. The transformation algorithm is as follows: (a) decreased motivation (NPI: apathy); (b) affective/emotional dysregulation (NPI: dysphoria, anxiety, and euphoria); (c) impulse dyscontrol (NPI: agitation/aggression, irritability/lability, and aberrant motor behavior); (d) social inappropriateness (NPI: disinhibition); and (e) abnormal perception/thought content (NPI: delusions and hallucinations).…”
Section: Methodsmentioning
confidence: 99%
“…In a community population-based study, MBI prevalence was 43.1% in subjective cognitive decline (SCD), and 48.9% in mild cognitive impairment (Mortby et al, 2018b). In a cognitive neurology clinic population, the prevalence was higher still at 76.5% in SCD, and 85.3% in MCI (Sheikh et al, 2018). If MBI is to detect those who are at high risk of incident cognitive decline and dementia for further assessment, workup or biomarker sampling, there is limited utility with these high frequencies.…”
Section: Introductionmentioning
confidence: 97%
“…The only study to address this question used the NPI as a proxy for MBI (by roughly mapping NPI items onto the five MBI domains) and found 3, 17, 16, 5 and 1% prevalence of apathy, mood/anxiety, impulse dyscontrol, social inappropriateness and psychosis respectively in cognitively normal individuals (Mortby et al, 2018b). A similar study but in a neurology clinic sample with subjective cognitive impairment (SCI), used a transformation of NPI-Q (a shorter version of the NPI) scores and reported significantly higher frequencies, likely to be in part a result of participants being sampled from a clinic rather than the general population in addition to the inherent limitations (described above) in using the NPI to rate MBI in non-dementia samples (Sheikh et al, 2018). Another major limitation is that the NPI is based on carer interview, which may not be appropriate for cognitively normal populations.…”
Section: Introductionmentioning
confidence: 99%